2015
DOI: 10.1088/0031-9155/60/17/6669
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Exradin W1 scintillator to determine Ediode 60017 and microDiamond 60019 correction factors for relative dosimetry within small MV and FFF fields

Abstract: In this work we use EBT3 film measurements at 10 MV to demonstrate the suitability of the Exradin W1 (plastic scintillator) for relative dosimetry within small photon fields. We then use the Exradin W1 to measure the small field correction factors required by two other detectors: the PTW unshielded Ediode 60017 and the PTW microDiamond 60019. We consider on-axis correction-factors for small fields collimated using MLCs for four different TrueBeam energies: 6 FFF, 6 MV, 10 FFF and 10 MV. We also investigate per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
83
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 34 publications
14
83
1
2
Order By: Relevance
“…To account for this effect, aČerenkov correction factor (CLR) has been measured following both the procedures suggested by the manufacturer for the different orientations of the scintillating fibre relative to the radiation beam axis. 22,30 Despite the difficulties of the four-step procedure recommended with the scintillator axis is orientated parallel to the beam axis (as mentioned by Underwood et al 24 ), by accurately controlling the positioning of the fibre, we found similar standard deviations, , 1%, which confirm data reported by Carrasco et al 28 , who performed the procedure with the detector perpendicular to the beam axis in plastic water. For convenience, we used the same approach for CLR calibration in the measurement sessions, with the detector perpendicular to the beam axis.…”
Section: Methodssupporting
confidence: 87%
See 2 more Smart Citations
“…To account for this effect, aČerenkov correction factor (CLR) has been measured following both the procedures suggested by the manufacturer for the different orientations of the scintillating fibre relative to the radiation beam axis. 22,30 Despite the difficulties of the four-step procedure recommended with the scintillator axis is orientated parallel to the beam axis (as mentioned by Underwood et al 24 ), by accurately controlling the positioning of the fibre, we found similar standard deviations, , 1%, which confirm data reported by Carrasco et al 28 , who performed the procedure with the detector perpendicular to the beam axis in plastic water. For convenience, we used the same approach for CLR calibration in the measurement sessions, with the detector perpendicular to the beam axis.…”
Section: Methodssupporting
confidence: 87%
“…The results are compared with those obtained with other detectors we already use for small photon beam dosimetry, contributing to complement data that can be found in the literature, 24,[27][28][29] in particular regarding the behaviour of these detectors in smallfield beam dosimetry required for TPS commissioning (PDD, dose profile and OF measurements).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Our measured data agree with results presented by Lechner et al (16) for Elekta linacs where there is minimal deviation in detector measured output factors between FFF and FF fields. Underwood et al (43) determined a similar deviation in small field correction factors for FFF and FF fields for a diode and the PTW microDiamond detector for a Varian linac.…”
Section: Discussionmentioning
confidence: 82%
“…The MC code was first validated against the square field measurements. There is currently no commercial scanning tank compatible with the PSD, (32) as a two‐channel output system is required to account for the Cerenkov light ratio correction with varying fiber lengths in the field. The Edge diode detector was thus utilized for PDD comparison against MC calculations, while EBT3 film measurements were used for the absolute dose profile comparisons.…”
Section: Resultsmentioning
confidence: 99%